The Effect of ICT Digital Picture Storybook Learning on The Global Diversity Dimension of Fourth-Grade Elementary Students - Kuswendi, Uus; Firdaus, Anugrah Ramadhan (PrimaryEdu : Journal of Primary Education, 2024)
This study aims to measure the dimensions of global diversity among fourth-grade students through the use of ICT digital picture storybooks in learning. Through digital picture story books, students can get to know and learn about the diversity of Indonesian culture so that the character of the Profil Pelajar Pancasila emerges in the form of a global diversity dimension. The research employs a quantitative approach with a quasi-experimental design, specifically the Pretest Posttest Nonequivalent Control Group Design. The sample consists of 40 fourth-grade elementary school students in Cimahi. Data collection was conducted using essay tests. The validity of the data was tested through content validity by seeking validation from experts. Data analysis was performed using inferential statistical tests, including normality tests, homogeneity tests, and t-tests. Additionally, an N-gain test was conducted to calculate the effectiveness of the learning method. The results show that ICT digital picture storybook learning has an effect on the global diversity dimension of fourth-grade students. This is evidenced by the significance value, which was 0.01. Furthermore, the N-gain test showed a value of 0.35, indicating that ICT digital picture storybook learning has moderate effectiveness